(untitled) (Revista Lusófona de Educação, 2025)
Brazil has a population of over 1.6 million Indigenous people. In 2008, Law 11.645 was enacted, mandating the inclusion of indigenous themes in the co2untry’s Basic Education. However, its implementation remains quite limited. This article advocates for the incorporation of the emic perspective—that is, the viewpoint of indigenous peoples themselves—into the training of History teachers as a strategy to promote inclusive edu cation in diverse contexts. Examples of academic work by indigenous scholars are presented, particularly the final research projects (TCCs) from the Intercultural Training Course for Indigenous Educators (FIEI) at the Fed eral University of Minas Gerais (UFMG), which provide valuable insights into the history and culture of various indigenous peoples. The promotion of the emic perspective is, therefore, a potential approach to fostering more pluralistic teaching, contributing to addressing the challenges of teacher training in diverse contexts. KEYWORDS: Emic perspective; Teacher training; Law 11.645/2008